Association between long Internet use during pregnancy and low birth weight: a retrospective cohort study - Sakakihara, Aya; Haga, Chiyori; Kinjo, Aya; Osaki, Yoneatsu (Environmental health and preventive medicine, 2024)
Low birth weight (LBW) is an important public health issue that affects development and health over a long period. However, there has been no sufficient decrease in the prevalence of LBW, and it is important to identify preventable factors for LBW which remain to be clarified. The purpose of this study was to clarify the association between Internet use for many hours during pregnancy and LBW. The subjects were mothers who had submitted the pregnancy notification form in Matsue City between April 2016 and September 2017 and their children. The data provided by Matsue City authorities consisted of 2,465 records. We analyzed 2,089 records, excluding untraceable records, those with insufficient information, those on multiple pregnancy, and those on pregnant smokers. Logistic regression analysis was performed using LBW as a dependent variable, Internet use for many hours during pregnancy as an independent variable, and the child's sex, mother's age at the time of pregnancy, unmarried status on pregnancy, first childbirth, mother's job during pregnancy, and weeks of pregnancy on the notification as covariates. The results of analysis showed that Internet use for many hours during pregnancy accounted for 4.4%, and that LBW accounted for 7.2%. Internet use for many hours during pregnancy was associated with LBW (adjusted odds ratio = 2.16 (95%CI: 1.13-4.13)). This study suggested that there is an association between Internet use for many hours during pregnancy and LBW. It is necessary to provide appropriate support to pregnant women who use the Internet for many hours during pregnancy after confirming the presence or absence of risk factors for LBW.